Difference between revisions of "Z score diff of mean"
From OPOSSEM
Line 1: | Line 1: | ||
<math> Z = \frac{\bar{y}_2 - \bar{y}_1 - 0}{s_{\bar{y}_2-\bar{y}_1}}</math>, where <math>s_{\bar{y}_2-\bar{y}_1} = \sqrt{\frac{(n_1-1)s_1^2+(n_2-1)s_2^2}{n_1+n_2-1}}\sqrt{{\frac{1}{n_1}}+{\frac{1}{n_2}}}</math> | <math> Z = \frac{\bar{y}_2 - \bar{y}_1 - 0}{s_{\bar{y}_2-\bar{y}_1}}</math>, where <math>s_{\bar{y}_2-\bar{y}_1} = \sqrt{\frac{(n_1-1)s_1^2+(n_2-1)s_2^2}{n_1+n_2-1}}\sqrt{{\frac{1}{n_1}}+{\frac{1}{n_2}}}</math> | ||
+ | |||
+ | |||
+ | <noinclude>[[Category:Equations]]</noinclude> |
Revision as of 07:04, 17 June 2011
<math> Z = \frac{\bar{y}_2 - \bar{y}_1 - 0}{s_{\bar{y}_2-\bar{y}_1}}</math>, where <math>s_{\bar{y}_2-\bar{y}_1} = \sqrt{\frac{(n_1-1)s_1^2+(n_2-1)s_2^2}{n_1+n_2-1}}\sqrt{{\frac{1}{n_1}}+{\frac{1}{n_2}}}</math>